The relationship between parental smartphone dependence and elementary students’ internet addiction during the COVID-19 lockdown in China: the mediating role of parent–child conflict and the moderating role of parental roles - Long, Chunlan; Liu, Junjie; Wu, Yupan; Liu, Siyang (Frontiers in Psychology, 2024)
During the COVID-19 lockdown in China, the shift of family members' work and study to online platforms accelerated internet proliferation and led to a growing prominence of internet addiction among younger age groups, posing a threat to individual and societal health development. Previous research has primarily focused on upper-grade elementary students, with relatively less attention given to younger age groups, resulting in insufficient representativeness of the elementary student samples. Additionally, research exploring how parental addictive behaviors are associated with the mechanisms of internet addiction among elementary students has been limited, which affects the development of scientifically based and effective intervention measures for addressing internet addiction in this population.This study, grounded in Family Systems Theory, explores the associative mechanisms between parental smartphone dependence and elementary students' internet addiction, specifically examining the mediating role of parent-child conflict and the moderating role of parental roles. Using a convenience sampling method, questionnaires were administered to parents from two elementary schools, resulting in 433 valid responses. Structural equation modeling analysis revealed that parental smartphone dependence is associated with elementary students' internet addiction and that this association is further influenced by the mediating role of parent-child conflict. Additionally, parental roles moderate the relationships between parental smartphone dependence and parent-child conflict, as well as between parent-child conflict and elementary students' internet addiction.Compared to mothers, fathers' smartphone dependence is more significantly correlated with parentchild conflict, and conflicts initiated by fathers are more strongly associated with elementary students' internet addiction. This may be related to China's traditional "male breadwinner, female homemaker" family culture. Mothers typically assume more parenting responsibilities and establish closer emotional bonds with their children, serving as a protective factor against internet addiction.Therefore, it is recommended that parents reduce smartphone dependence to avoid parentchild conflicts, and that fathers increase their involvement in parenting activities to build stronger emotional connections with their children, thereby fostering healthier internet use behaviors among elementary students. The findings provide valuable insights for developing effective family-based interventions to address internet addiction in children.